HUBUNGAN KEMANDIRIAN DENGAN MINAT BERWIRAUSAHA SISWA SEKOLAH MENENGAH KEJURUAN NEGERI 1 SEWON BANTUL YOGYAKARTA - Rumswasti Dhaneswari (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2016)
The objectives of this research are toknow (1) illustration independence of entrepreneurship, (2) illustration interest of entrepreneurship, and (3) the correlation of independence and interest in entrepreneurship atthe Students of Vocational Public School 1Sewon Bantul Yogyakarta. The type of theresearch is ex-post facto. Data are collectedby questionnaire and documentation. Dataanalysis techniques: descriptive analysis andhypothesis test used product moment correlation begun by prerequisite analysis, that isnormality and linearity examination. The results show that independence is categorizedhigh by relative frequency 45,23%, and theinterest of entrepreneurship is fair by relativefrequency 55,95%. Based on correlation test,the score of rxy was 0,493. The score of r tablein the significant level 5% for total respondents 84 was 0,214 (rxy 0,493> r table 0,214).It means that there was a positive and significant of independence and interest in entrepreneurship. The score of determinant coefficient(R2) was 0,244, it means that independenceand interest in entrepreneurship gave a positive contribution 24,4% toward family healthfood service, while 75,6% was influenced byother factors that were not analyzed in thispaper.